Avaliação da atividade fotodinâmica de compostos porfirínicos sobre micro-organismos patogênicos - Piasentin, Fernanda Baldissera (2018)
Introduction: The increase of microbial resistance to conventional treatments and the increasingly frequent appearance of multiresistant microorganisms has encouraged studies to develop new techniques able to overcome the advance of this problem. Therefore in recent years photodynamic therapy has emerged as an efficient alternative in the inactivation of Gram- positive and gram-negative bacteria, as well as with fungi and viruses. This technique combines a photosensitizer, with light and oxygen, leading to the formation of cytotoxic species (atomic oxygen and free radicals) that damage the cell membrane of these microorganisms causing microbiological inactivation. Objectives: Evaluate, in vitro, the photodynamic activity antimicrobial promoted by compounds derived from ferrocene-porphyrins against pathogenic microorganisms. Material and methods: Strains of E. coli ATCC 25922, S. aureus ATCC 25923, P. aeruginosa ATCC 27853, S. epidermidis ATCC 1228, S. wernicke, B. cereus ATCC 14579, B. subtilis ATCC 19559, five strains of MSSA and six strain MSSA, C. albicans ATCC 14057, A. fumigatus CBS 133-61 and Prototheca spp which were exposed to photosensitizers: TPP, TFcP, ZnTFcP, at concentrations of 6.0 μM, 3.0 μM and 1, 5 μM. After adjusting the inoculum, 100μL of the cell suspension and 100μL of the photosensitizer were placed in 96- well microplates, incubated in the dark for 30 min at 30°C (±2°C), under agitation and then exposed to light for 1 minute and 50 seconds. Aliquots of 10μL were removed and seeded at 35°C until growth and after the number of developing colonies was determined. Results and discussion: The photodynamic activity of TPP, TFcP and ZnTFcP in the three concentrations tested was able to inhibit bacteria growth only of S. aureus species ATCC 25922, S. wernicke, S. epidermidis, B. cereus ATCC 14579, in the MRSA strains, whereas for the MSSA strains, the best combination occurred when the light was used with TFcP at the concentration of 3.0 μM, and for B. subtilis ATCC 19559, PDT was effective only TPP at concentrations of 1.5 μM and 3.0 μM. For gram-negative bacteria, fungi and Prototheca spp, there were no results classified as satisfactory. Possibility this is due to the structure of the cell membrane of gram- negative bacteria, fungi and algae being more complex, turning difficult the entrance of photosensitizers into the cells, as well as the disruption of the cytoplasmic membrane. Another factor that contributed to the absence of a significant reduction in the growth of microorganisms is the absence of charge of the photosensitizers, because the presence of charge facilitates the cellular penetration as well as its accumulation inside the cell. Conclusion: The photodynamic inactivation of microorganisms may become an alternative treatment, however, the investigations focused on photosensitizers deserve attention in order to obtain better results.